Formulation and Stability Testing of Griseovulfin Microemulsion - iyan sopyan; Dolih Gozali; Eka Paramudya (Universitas Padjadjaran (Unpad), 2020)
The use of drugs that are less soluble in water will become clinically less efficient, this is caused by the low penetration of the drug into the body. A microemulsion is a dispersion system such as an emulsion that can increase the solubility of drugs that are sometimes difficult to dissolve in water. Microemulsions have long-term stability, clear, transparent, and good penetration capabilities. In this study, a microemulsion formulation with active ingredients griseofulvin and virgin coconut oil was conducted as an oil phase. The resulting microemulsion evaluates physical stability during 35 storage days. The results showed that the microemulsion preparation remained stable during storage time without changes in color, odor, and consistency, while the pH and dosage viscosity experienced less significant changes. The consequences of the centrifugation test at 3700 rpm for 5 hours and freezing tests for 24 days showed stable preparation and cannot be separated. The diffusion test results obtained by FG2 had the largest permeation percentages of 3.6136%, FG3 2.8724%, and the smallest FG1 2.0477%.Keywords: microemulsion, griseofulvin, stability, diffusion test